Evaluasi Rasionalitas Penggunaan Antibiotik Infeksi Saluran Kemih Bawah di Rsd Gunung Jati Cirebon Periode Januari–Desember 2022 - Efriani, Like; Irawan, Ade; Yunita, Fina (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Urinary tract infection is an infection caused by the presence of microorganisms in the urinary tract, including the prostate bladder. Antibiotics are drugs to treat infections caused by bacteria. Giving antibiotics to people with infectious diseases aims to inhibit the growth or kill microorganisms, especially bacteria that cause disease. The aim of this research is to find out whether giving medication to patients with lower urinary tract infections at RSD Gunung Jati is rational or irrational. This research was carried out in an analytical observational manner using a retrospective research design, namely by taking patient data from medical records and prescriptions for patients suffering from lower urinary tract infections at RSD Gunung Jati, Cirebon City for the period January-December 2022. The number of samples in the study was 85 samples. according to the inclusion criteria. Statistical analysis used in this research is chi-square and mann whitney. The parameters taken in this study were the right dose, the right diagnosis, the right indication, and the right drug. The results of the study showed that lower urinary tract infections were mostly experienced by women, amounting to 58 people (68%), sufferers of lower urinary tract infections were mostly experienced by patients aged 46-55 years, amounting to 22 patients (26%). The drug most commonly received by patients with lower urinary tract infections was cefixime, 49 times (53%). Most patients with lower urinary tract infections were given in single form in 84 people (99%). Patients suffering from lower urinary tract infections most often experienced symptoms of pain when urinating, with 71 patients (47%). The evaluation results showed that the right dose by 96%, the right drug by 100%, the right indication by 100%, and the right diagnosis by 100%. In the statistical analysis, the results showed that the medication given to patients with lower urinary tract infections met the rational requirements and had a significant rationality value.